Cytogenetic study of subtypes of Down syndrome and its relation with pattern of congenital cardiac defects - Haider, Areiba; Sarah Khan; Raafea Taweez Kuraishi; Muhamamd Shahid Akhtar (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the frequency of subtypes of Down syndrome by karyotyping, and to establish the frequency of congenital cardiac defects in this population. Method: The cross-sectional study was conducted at the Department of Genetics, Children Hospital, Lahore, Pakistan, from June 2016 to June 2017, and comprised Down Syndrome patients aged <15 years. They were subjected to karyotypic analysis for determining the subtype of the syndrome, and echocardiography of all cases was done for the assessment of congenital cardiac defects. The two findings were subsequently used to establish a relation between the subtypes and congenital cardiac defects. Data collected, entered and analyzed by the SPSS version 20.0. Results: Among the 160 cases, trisomy 21 was found in 154(96.2%), translocation 5(3.1%) and mosaicism 1(0.6%). Overall, 63(39.4%) children had cardiac defects. Among such patients, patent ductus arteriosus was most common 25(39.7%), followed by ventricular septal defects24(38.1%), atrial septal defects16(25.4%), complete atrioventricular septal defects 8(12.7%), and tetralogy of Fallot3(4.8%), while 6(9.5%) children had other defects. Atrial septal defects was the most common double defect 9(56.2%) and had the highest coexistence with patent ductus arteriosus in Down syndrome cases with congenital cardiac defects. Conclusion: In Trisomy 21, the most common cardiac defect was patent ductus arteriosus, followed by ventricular septal defects isolated defects, whereas in mixed defects, atrial septal defects and patent ductus arteriosus were the highest. Key Words: Down syndrome, Congenital cardiac defects, Karyotyping, Children Hospital, Lahore.